Inverse domination in bipolar fuzzy graphs. (2021) - Kalaiselvan, S.; Vinoth Kumar, N.; Revathy, P.
Abstract: In this paper, we bring together the idea of an inverse domination in bipolar fuzzy graphs (BFG). A set I ⊆ V is supposed to be an inverse dominating set IDS in BFG's G ( V, E ) if D ⊆ V is a dominating set of G and I ⊆ ( V - D ) is a dominating set of V - D . The least among all the IDS's is called an inverse domination number γ B - 1 ( G ) of G ( V, E ) . Further study the bounds and characteristic of an inverse domination number (IDN) in various BFG.